Sosialisasi Penggunaan Kawat Anyaman Pada Bangunan Tahan Gempa Di Desa Karang Bayan Kabupaten Lombok Barat - Mahmud, Fathmah; Hariyadi, Hariyadi; Merdana, I Nyoman; Ngudiyono, Ngudiyono; Kencanawati, Ni Nyoman (Universitas Mataram, 2024)
In Lombok, West Nusa Tenggara, major earthquakes triggered by transform margin or plate shift often arise, leading to casualties, not only claiming lives but also affecting the livelihood of locals. Karang Bayan Village is a region division of Segerongan Village, these areas are often affected by major earthquakes, the last one took place not too long ago, in 2018. Due to its area located on the mountain slope of Rinjani, Karang Bayan has captivating scenery with a rather mild temperature, making it a perfect tourist destination. Karang Bayan offers various tourist attractions, starting from tours of traditional houses, durian orchards, horse riding, rafting, waterfalls, and many more to explore around the village. To boost tourism, Karang Bayan needs to establish proper accommodations along with other tourist facilities like restaurants. Ferrocement-coated buildings are suitable options considering their strength to withstand an earthquake. Mesh wire application on a ferrocement is more economical and practical compared to applying reinforced columns, reinforced beams, or beam-column joints reinforcement detailing. Both planning and construction are integral parts of founding strong buildings, miscalculations will pose threats to the inhabitants of the building. Karang Bayan community has limited knowledge of mesh-wired ferrocement walls for earthquake-resistant buildings, this community service is carried out in the hope people of Karang Bayan will be capable of constructing earthquake-resistant buildings with mesh-wired ferrocement walls. Positive feedback is shown by enthusiastic discussion between the Karang Bayan community with the community service team.